The Role of Academic Archives: Prospects and Possibilities (The Case of Nazarbayev University) - Yap, Joseph M. (Ministry of Culture and Sport of the Republic of Kazakhstan; National Academic Library of the Republic of Kazakhstan, 2018)
This article will take a look on the current status of adapting an academic archives for the Nazarbayev University as the main repository of historical intellectual content, an imprint of institutional legacy, and safeguards a wealth of information that preserves the academe’s social memory.
Keywords: academic archives; social memory; history